Surgical patients’ knowledge and acceptance of autologous blood transfusion (2008)
Background: Homologous blood transfusion carries a well-documented array of risks especially in an HIV endemic environment like Nigeria. It is therefore imperative to consider other forms of restoring blood volume in surgical patients. Autologous blood transfusion (ABT) is one of the ways the problem of HIV transmission can be reduced among surgical patients. The knowledge and acceptability of ABT among surgical patients about ABT, especially pre-donated ABT were assessed. It also assessed whether or not surgeons inform elective surgical patients about this alternative Materials And Methods: Questionnaires were distributed among elective surgical patients that presented during the study period. The knowledge, willingness and the factors influencing the willingness of the patients to participate in ABT were investigated. The data were analyzed with SPSS Version10. Results: Of the 116 patients [71 males; 45 females] interviewed, 29 (25.0 %) had heard about ABT, 80 (69.0 %) patients had never heard about ABT while 7 (6.1 %) were not sure. Of the 29 respondents who had heard about ABT, only 2 had had ABT. Of the 48 patients who needed blood for current surgical problems, only 4 (9.3 %) would have ABT. There was a significant difference in the number of respondents who believed that ABT is better than homologous transfusion (x2 = 69.11, p < 0.001). Conclusion: The knowledge of ABT is low among our surgical patients and surgeons should present this alternative to their patients. The acceptance of ABT may also help in reducing or eliminating HIV transmission via blood transfusion